2018
DOI: 10.1007/s10745-018-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

“Fish Rescue us from Hunger”: the Contribution of Aquatic Resources to Household Food Security on the Rufiji River Floodplain, Tanzania, East Africa

Abstract: Inland fisheries are essential to nutrition and food security in developing countries but remain undervalued. Worldwide, studies of aquatic resource consumption are rare. 'Fish rescue us from hunger' MS 2 We use data from a monthly survey of 40 households over one year in a Tanzanian village, combined with qualitative methods, to analyse consumption of animal aquatic resources across wealth, seasons, fishing vs. non-fishing and male-vs. female-headed households. We find that local freshwater fish are the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
0
22
2
Order By: Relevance
“…The study also discovered that family income have positive impact on fish intake. In a study carried out by Moreau and Garaway (2018), it was found that rich households consume larger quantities of fish than poor households. In another study, Verbeke and Vackier (2005) stated that poor income group have low fish consumption frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also discovered that family income have positive impact on fish intake. In a study carried out by Moreau and Garaway (2018), it was found that rich households consume larger quantities of fish than poor households. In another study, Verbeke and Vackier (2005) stated that poor income group have low fish consumption frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research investigations has been undertaken regarding the role of fish in the provision of high quality protein and nutritional security, to low income people particularly in less developed countries. Majority of research studies on fish consumption have based their investigation on the nutritional importance of fish meat (Belton et al, 2018;Bennett et al, 2018;Moreau and Garaway, 2018;Akuffo and Quagrainie, 2019;Mohanty et al, 2019;Kwasek et al, 2020). Some studies have investigated the impact of socioeconomic and demographical factors on people's fish intake (Oliveira et al, 2010;Perez-Cueto et al, 2011;Onurlubas, 2013;Can et al, 2015;Zhou et al, 2015;Kızıloğlu and Kızılaslan, 2016;Wenaty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite it having been seen as a key area for research (FAO, ; Hortle, ) and despite weights in many countries not being a common way of either describing fish size or of measuring quantities for sale, with people instead using “pieces,” “bunches,” “sticks,” “bowls” or “sacks” (e.g. Brugere, ; Moreau & Garaway, ).…”
Section: Introductionmentioning
confidence: 99%
“…It compares the accuracy and precision of two methods of collecting catch data over a short (<24‐hr) recall period: (a) the most common method used; asking informants to recall the weight of fish caught in grams and (b) using visual aids (VAs) that have been called “fish sticks” (sticks of different and known lengths) that assist respondents to recall the lengths of fish caught, recording those lengths, and then subsequently converting the lengths to weights using established length/weight relationships (either estimated locally or obtained from databases such as FishBase). The fish stick methodology for estimating yields and/or fish consumption was developed for household fish catch and consumption studies in Lao PDR (Garaway, ) and has been used in several studies since (Garaway et al, ; Moreau & Garaway, ). It is designed to take advantage of the fish length being far easier to represent in the form of a visual aid than fish weight, and given the recognised role of VAs/PSEAs in improving recall accuracy (Subar et al, ), this may improve results.…”
Section: Introductionmentioning
confidence: 99%